A Neoliberal Keynes?. Issue 3 (2nd October 2018) - Henry, John F.
Abstract: The standard perspective of post-Keynesians and others is that John Maynard Keynes represents an alternative (and antidote) to the neoliberal theory and practice that has dominated the world economy since the 1970s. The position taken in this article is that Keynes actually represents one version of neoliberalism s (plural), but a version that is hostile to that promoted by the dominant form of neoliberalism represented by theorists such as Milton Friedman and other Chicago economists. Keynes's version, shorn of specific technical features, is similar to several variants of neoliberal arguments. In this article, neoliberalism as an ideology will be evaluated, and the relation between neoliberalism s and society in general will be examined.